1988
DOI: 10.1159/000205729
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Lymphoma Showing Clinicopathological Features of Malignant Histiocytosis

Abstract: This report describes a case of B cell lymphoma, the clinicopathological features of which are quite similar to those of malignant histiocytosis. The clinical features included fever, anemia, and marked hepatosplenomegaly without lymphadenopathy. Histological findings revealed diffuse and noncohesive proliferation of cytologically atypical cells and benign-appearing histiocytes in the splenic red pulp, where the erythrophagocytosis was frequently found. Immunological studies, however, revealed a B cell nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 5 publications
(6 reference statements)
3
13
0
Order By: Relevance
“…However, autopsies of two cases revealed histopathologic findings which were characteristic of IVL. Based on these observations, careful investigation of the other three cases of the present series and the nine cases previously described as MH-like BCL in the Japanese literature (Kuratsune et al, 1988;Sakai et al, 1991;Imai et al, 1992;Iwahashi et al, 1992;Takeshita et al, 1993;Yamada et al, 1996) suggests that most of them might fall within the framework of IVL and form a distinct variant.…”
supporting
confidence: 52%
“…However, autopsies of two cases revealed histopathologic findings which were characteristic of IVL. Based on these observations, careful investigation of the other three cases of the present series and the nine cases previously described as MH-like BCL in the Japanese literature (Kuratsune et al, 1988;Sakai et al, 1991;Imai et al, 1992;Iwahashi et al, 1992;Takeshita et al, 1993;Yamada et al, 1996) suggests that most of them might fall within the framework of IVL and form a distinct variant.…”
supporting
confidence: 52%
“…2 In many lymphomas associated with HPS, tumor cells were of T cell origin; 3-5 but some cases of B cell lymphoma-associated HPS have also been reported. [6][7][8][9] Wong and Chan 10 retrospectively analyzed 40 HPS cases and found 16 lymphoma cases (T lineage, six; B lineage, three; lineage not determined, seven). Similar to the present case, HPS was the initial presentation of the lymphoma in 10 of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Before the advent of immunohistological examination, the absence of mass formation and the diffuse infiltration of large neoplastic cells into the red pulp might have been diagnosed as malignant histiocytosis [3]. Kuratsune et al [4] reported the first case of DLBCL that non-cohesively proliferated into the splenic red pulp and demonstrated clinicopathological features of malignant histiocytosis. Since their initial report, only 18 cases of DLBCLs non-cohesively infiltrating the splenic red pulp have been reported [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the features of this rare lymphoma, we describe six new cases of DLBCLRP and present an analysis of the clinicopathological features of an additional 18 previously reported cases [4][5][6][7][8][9][10][11][12][13]. After reviewing the data, we developed seven characteristic features of DLBCLRP.…”
Section: Introductionmentioning
confidence: 99%